2006
DOI: 10.1007/s10534-006-9018-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress response in two strains of the aquatic hyphomycete Heliscus lugdunensis after exposure to cadmium and copper ions

Abstract: Biochemical responses to cadmium (Cd2+) and copper (Cu2+) exposure were compared in two strains of the aquatic hyphomycete (AQH) Heliscus lugdunensis. One strain (H4-2-4) had been isolated from a heavy metal polluted site, the other (H8-2-1) from a moderately polluted habitat. Conidia of the two strains differed in shape and size. Intracellular accumulation of Cd2+ and Cu2+ was lower in H4-2-4 than in H8-2-1. Both strains synthesized significantly more glutathione (GSH), cysteine (Cys) and gamma-glutamylcystei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 54 publications
4
42
0
3
Order By: Relevance
“…In barley plants, Finkemeier et al (2003) observed a 50% reduction of glutathione reductase activity under cadmium exposure depending on external N availability. Decline in GR activity after heavy metals treatment was also reported by Braha et al (2007);Tripathi et al (2006). GR did not respond to heavy metal exposure could be explained by the fact that its constitutive activity was sufficient to maintain glutathione in a reduced state (Sharma et al 2004) and/or through metal binding to SH-groups at the active site of the enzyme (Nagalakshmi and Prasad 2001).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In barley plants, Finkemeier et al (2003) observed a 50% reduction of glutathione reductase activity under cadmium exposure depending on external N availability. Decline in GR activity after heavy metals treatment was also reported by Braha et al (2007);Tripathi et al (2006). GR did not respond to heavy metal exposure could be explained by the fact that its constitutive activity was sufficient to maintain glutathione in a reduced state (Sharma et al 2004) and/or through metal binding to SH-groups at the active site of the enzyme (Nagalakshmi and Prasad 2001).…”
Section: Discussionmentioning
confidence: 77%
“…GR did not respond to heavy metal exposure could be explained by the fact that its constitutive activity was sufficient to maintain glutathione in a reduced state (Sharma et al 2004) and/or through metal binding to SH-groups at the active site of the enzyme (Nagalakshmi and Prasad 2001). Later idea seems to be rejected by some authors who concluded that direct interference by the metals can be excluded, since adding Cd or Cu to the test tube did not affect enzyme activities (Braha et al 2007). Another reason for decreased glutathione reductase activity could be a lack of redox equivalents such as NADPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that microbial decomposition is mainly governed by fungi PASCOAL et al, 2005a), and fungi may canalize part of their energy towards defence mechanisms against metal stress (AZEVEDO et al, 2007(AZEVEDO et al, , 2009BRAHA et al, 2007;GUIMARÃES-SOARES et al, 2007), it is plausible that fungal biomass and/or reproduction could be affected with possible impacts to leaf litter decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic hyphomycetes respond to metal exposure or other forms of stress by synthesizing various thiol-containing proteins/peptides, phytochelatins, heat shock proteins, and antioxidiants [33][34][35][36]. Type and magnitude of these counteradaptations are generally species specific.…”
Section: Discussionmentioning
confidence: 99%